"SCAFFOLDING" STUDENTS WRITING IN EFL CLASS: IMPLEMENTING PROCESS APPROACH - Ekaning Dewanti Laksmi (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
The writing process approach views a writing learner as a creator of text, and hence, he needs to experience what writers actually do as they write, and so do students in EFL writing classes. The approach offers an answer to the need of helping the students develop their writing skill without their having to master the basic fundamental elements of writing, i.e. grammar, prior to attending the writing courses. This article highlights the potential of the process approach-with which students go through a write-rewrite process-in giving students a scaffold to work in a real, live process of how a real writer engages in the process of writing. However, the most important harvest is the fact that students have become more confident in expressing their ideas in writings.